PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA ELEMEN BHINNEKA TUNGGAL IKA MENGGUNAKAN MODEL TEAM GAMES TOURNAMENT DI KELAS V SD SEMEN PADANG - Nadifa, Efrilia; Anita, Yesi; Reinita; Zahara, Leni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in Pancasila Education learning in grade V of Semen Padang Elementary School, which is caused by the lack of use of innovative learning models, low student involvement, and suboptimal learning planning. This research aims to improve student learning outcomes in the elements of Bhinneka Tunggal Ika through the application of the Team Games Tournament learning model. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, including the planning, implementation, observation, and reflection stages. The research subjects are teachers (researchers) and 22 students consisting of 12 male students and 10 female students. Data were collected through observation, tests, non-tests, and documentation, then analyzed descriptively quantitatively and qualitatively. The results of the study showed an increase in each cycle: 1) RPPM cycle I averaged 89.55% with a grade of B (Good) increasing in cycle II to 95.83% with a grade of SB (Very Good), 2) Implementation of teacher activities cycle I 87.49% with a grade of B (Good) increasing in cycle II to 96.42% with a grade of SB (Very Good), then, implementation of student activities cycle I averaged 87.49% with a grade of B (Good) increasing in cycle II to 96.42% with a grade of SB (Very Good), 3) Assessment of students in improving learning outcomes in cycle I averaged 76.04% with a grade of K (Less) increasing in cycle II to 89.64% with a grade of B (Good).